Mitigating Academic Speaking Anxiety by Using WhatsApp Voice Notes for Academic Speaking Class - Siti Nur Halizah; Endah Nur Tjendani; Fatih Al Fauzi (UIBU, 2025)
Speaking anxiety is one of the primary barriers to students' spoken communication and active engagement in English lessons. Despite substantial research on alleviating speaking anxiety, most prior studies have primarily employed quantitative or mixed-methods approaches, which often provide limited insight into the ongoing process of change within the classroom. To address this gap, this study aims to investigate the use of WhatsApp Voice Notes as an educational tool to mitigate students' academic speaking anxiety, employing an ongoing and reflective teaching methodology. This study uses a qualitative approach and employs Classroom Action Research (CAR) with purposive sampling of PBI 4th-semester students, consisting of 6 participants. This study involved observations, questionnaires, and an interview to identify and characterize the speaking anxiety Symptoms seen during the intervention session. The findings indicated a significant reduction in anxiety symptoms from Cycle 1 to Cycle 2, encompassing diminished nervousness, trembling, and confusion. This study highlights how WA VN can be an effective digital support tool that significantly reduces academic speaking anxiety by cultivating a low-anxiety online speaking environment. It provides instructors with practical insights by positioning WVN as an economical and adaptable resource that can strengthen students' speaking confidence and provide a friendly, technology-enhanced learning environment.